2021
DOI: 10.2147/ijgm.s315827
|View full text |Cite
|
Sign up to set email alerts
|

Association of Short and Long Interpregnancy Intervals with Adverse Birth Outcomes: Evidence from a Cross-Sectional Study in Northwest China

Abstract: Purpose To analyze the effects of a short interpregnancy interval (IPI) (<6 months) and a long IPI (>120 months) on neonatal adverse birth outcomes including low birth weight (LBW), small for gestational age (SGA), preterm birth (PTB), and birth defects in Shaanxi Province. Patients and Methods A stratified multistage random sampling method was used to recruit participants who gave birth between 2010 and 2013 in Shaanxi province. A self-designed questionnaire was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…However, a few unmatched studies in China have presented inconsistent results compared with the unmatched analysis. For example, Shi et al 23 used a generalized linear model to explore the association of IPI with adverse perinatal outcomes in Northwest China; they found that a shorter IPI of less than 6 months was associated with higher risks of SGA but not PTB and LBW. A possible explanation for such differences is that different sample sizes and adjustment factors were involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a few unmatched studies in China have presented inconsistent results compared with the unmatched analysis. For example, Shi et al 23 used a generalized linear model to explore the association of IPI with adverse perinatal outcomes in Northwest China; they found that a shorter IPI of less than 6 months was associated with higher risks of SGA but not PTB and LBW. A possible explanation for such differences is that different sample sizes and adjustment factors were involved.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study period was restricted from 2014 to 2020, which resulted in a relatively limited amount of data on long IPI (>60 months), making it difficult to explore the association between long IPI and adverse perinatal outcomes. Second, consistent with previous studies, this study included only live, consecutive, single-birth data. Thus, these results might not apply to women who had experienced a miscarriage or stillbirth between deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings have been reported elsewhere. 2,6 Despite the fact that prolonged IPIs might allow more complete recovery of the mother, 30 researchers have also opined that pregnancy intervals longer than 5 years might lead to poor infant outcomes, such as preterm birth, small-for-gestational-age fetus, LBW, NICU admission, and stillbirth. 12,30 A recent study of adverse consequences associated with an IPI of 60 months or greater has illustrated that physiologic adaptations of the reproductive system regress gradually after a long time if a woman does not conceive another fetus, which in turn may revert the mother's physiology to a state similar to primigravidity.…”
Section: Discussionmentioning
confidence: 99%